IMMUNOCHEMICAL STUDIES ON THE ANTIGENIC DETERMINANTS REQUIRED TO ELICIT DELAYED AND IMMEDIATE HYPERSENSITIVITY REACTIONS - Schlossman, Stuart F. (The Rockefeller University Press, 1966)
Hartley and strain 2 guinea pigs were sensitized to chemically defined α-DNP(Lys)(n)-BuAm, α-DNP(Lys)(n)-, and (Lys)(n)-BuAm peptides and skin tested with individual members of these homologous series, related peptides and hapten-substituted proteins. The immediate skin response (Arthus) could be elicited with hapten-substituted tetra-, penta-, or hexamers, whereas both immediate and delayed skin responses could be provoked by the octamer or nonamer. The hapten is an integral part of the determinant for both immediate and delayed skin reactivity, since poly-L-lysine was unable to elicit either delayed or immediate reactions in sensitized animals. Arthus type cross-reactions occurred only when the sensitizing and test antigen shared a common haptenic determinant. In contrast to this, in this system, delayed type cross-reactions occurred only when the test antigen and the sensitizing antigen contained both a large oligo-L-lysine carrier as well as the same haptenic determinant. These observations imply that the mediation of the delayed response requires a larger determinant than is necessary to elicit the immediate response. The role of high affinity antibody as the mediator of the delayed response is discussed in terms of the size of the antigenic determinants required to elicit this response. It was found that the ability to elicit the delayed response paralleled the immunogenic capacity of these peptides, whereas the immediate response could be elicited by nonimmunogenic peptides. This finding suggests that the delayed response may require the continued biosynthesis of antibody and may be analogous to a local in vivo secondary response.